2001
DOI: 10.1097/00001756-200110290-00023
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of the synaptosomal associated protein SNAP-25 in hippocampus of subjects with mood disorders and schizophrenia

Abstract: SNAP-25 levels were measured in ventral hippocampus in subjects with unipolar depression (n = 12), bipolar disorder (n = 13), schizophrenia (n = 15) and controls (n = 15) using quantitative immunocytochemistry. SNAP-25 levels were reduced significantly in stratum oriens of bipolar patients compared with controls (p < 0.05); they were also reduced significantly in st. oriens (p < 0.01 vs schizophrenia), in alveous (p < 0.01 vs schizophrenia) and in presubiculum (p < 0.05 vs depressed). SNAP-25 levels were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 28 publications
3
55
0
1
Order By: Relevance
“…52,53,59,60 The alterations in the protein levels of DISC1, LIS1 or SNAP-25 were found in 7-day-old mouse pups and were no longer present in older mice. This developmental pattern is in accordance with the available data that early and transient disruptions in the developmental programs during brain development can produce a behavioral disease that manifests in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…52,53,59,60 The alterations in the protein levels of DISC1, LIS1 or SNAP-25 were found in 7-day-old mouse pups and were no longer present in older mice. This developmental pattern is in accordance with the available data that early and transient disruptions in the developmental programs during brain development can produce a behavioral disease that manifests in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…56 Additionally, DYN-I has also been found to interact with NMDA receptor 1 57 and SNAP-23, 58 closely related to SNAP-25, proteins which have been previously implicated in the pathogenesis of schizophrenia. [59][60][61][62] DYN-I is a GTPase essential for the recovery of synaptic vesicles from the neuronal membrane once the contents have been released 63 and has been hypothesized to have evolved to have a primary role in synaptic vesicle recycling. 64 ), who found that DYN-I and II were increased in the grey matter but decreased in the white matter of schizophrenics in comparison to controls, while a recent proteomics study of the anterior cingulate cortex in schizophrenia also reported an increase in dynamin 1 in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…These include parvalbumin, 8 the complexins, 32 glucocorticoid receptors, 33 NMDA-NR1 receptors, 34 and SNAP-25. 35 Tyrosine receptor kinase A (trkA) was decreased in CA2 and CA4 in schizophrenia and bipolar disorder. TrkA and its ligand, nerve growth factor (NGF), have been suggested to be involved in severe mental illness based on preliminary observations in animals and in plasma studies in humans; 36,37 however, genetic and postmortem studies supporting a role for trkA or NGF are lacking.…”
Section: Discussionmentioning
confidence: 99%